(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to investigate the anti-diabetic activity of biscuits containing ethanolic extract of whole plant of Cissus quadrangularis linn. in diabetic rats induced by alloxan. Alloxan-induced diabetic rats received ethanolic extract (EECQ) and biscuits (BEECQ) containing ethanolic extract of Cissus quadrangularis linn. and glibenclamide via oral administration. The plasma glucose level was assessed at 0, 3, 6, 9 and 12 h after drug administration. The EECQ and BEECQ (30 mg/kg) showed critical decrement in plasma glucose level as compare to vehicle treated group. Results revealed that ethanolic extract of whole plant of C. quadrangularis linn. has anti-diabetic activity.